Academic Reinforcement for Producing Elementary Teachers by Design Thinking Approach and Professional Learning Community - Suwankitti, Sasiwan (Ratchaphruek Journal, 2022)
This research was a study of an academic reinforcement for producing elementary teachers of Rajabhat University based on CCR-Contemplative Education, Coaching and Research-based learning by design thinking approach, and professional learning community. The purposes were to: 1) Develop an academic reinforcement for producing elementary teachers; and 2) Study the results of the academic reinforcement. The samples comprised of 20 lecturers in Elementary department of 3 Rajabhat Universities which were selected by volunteer, 125 fourth year student teachers in academic year 2020 from the sample teachers, and 115 student teachers’ mentors. Research instruments were the assessment forms of CCR’ understanding, teacher characteristics, learning management competency, coaching competency, and reflective writing form. Quantitative data were analyzed by mean, standard deviation and compared with criteria level, and qualitative data were analyzed by analytic induction. The study revealed that: 1) the academic reinforcements were the empathy of samples consisted of lecturers, student teachers, and student teachers’ mentors, the definition of problems, the idea, and 3 stages prototypes. 2) The results of academic reinforcement were found that all samples’ CCR understanding, teacher characteristics, learning management competency, and coaching competency were higher competency level than before participating the project. The processes of producing CCR elementary teachers were self-consciousness, understanding in CCR, pattern creation, experience, and reflection.